Bioinspired human stomach-on-a-chip with in vivo like function and architecture. Issue 3 (9th January 2023) - Ferreira, Daniel A.; Conde, João P.; Rothbauer, Mario; Ertl, Peter; Granja, Pedro L.; Oliveira, Carla
Abstract : A biomimetic stomach-on-a-chip with integrated peristalsis-like motion and intra-luminal flow. Application of dynamic conditions, elicited differentiation traits that are typical of the normal gastric mucosa, but otherwise lost in 2D culture models. Abstract : The lack of biomimetic in vitro models capable of reproducing the complex architecture and the dynamic environment of the gastric mucosa, delay the development of diagnostic and therapeutic tools. Recent advances in microengineering made possible the fabrication of bioinspired microdevices capable of replicating the physiological properties of an organ, inside a microfluidics chip. Herein, a bioinspired stomach-on-a-chip (SoC) device is described, supporting peristalsis-like motion and reconstituting organ-level epithelial architecture and function. The device simulates the upper epithelial interface, representing the three innermost layers of the gastric mucosa, namely the epithelial barrier, the basement membrane and the lamina propria. The dynamic environment imparted by mechanical actuation of the flexible on-chip cell culture substrate, was the main driver in the development of epithelial polarization and differentiation traits characteristic of the native gastric mucosa, and allowed partial recapitulation of gastric barrier function. These traits were not affected by the addition of a mesenchymal population to the system, which was able to remodel the surrounding extracellular matrix, nor by the potential epithelial–mesenchymal cross-talk. The engineered platform highlights the importance of addressing the mechanical microenvironment of the native organ, to potentiate an organ-level response of the artificial tissue. The proposed SoC represents an appealing tool in personalized medicine, with bio-relevance for the study of gastric diseases and an alternative to current animal models.